Wild-caught Hybrids Between Sailfin and Shortfin Mollies (Poeciliidae, Poecilia): Morphological and Molecular Verification - Kittell, Michele M.; Harvey, Megan N.; Contreras-Balderas, Salvador; Ptacek, Margaret B. (HIDROBIOLÓGICA, 2017)
This study documents four wild-caught, interspecific hybrids between sailfin mollies (Poecilia velifera or P. petenensis) and shortfin mollies (P. mexicana or P. orri) from the Yucatán peninsula and Isthmus of Tehuantepec regions of México. In canonical discriminant analysis of morphological data all four putative hybrid males were intermediate in shape between shortfin and sailfin molly species, falling well outside 95% confidence ellipses for those putative parental species. For two of the four hybrid individuals, we used allele size differences at the nuclear Xsrc gene between sailfin and shortfin species to determine that one was a first (F1) or early generation (F2, BC1) hybrid and the other was a later generation (>F1) hybrid. Sequences of the mtDNA control region (483 bp) and Xsrc nuclear gene (636 bp) indicated that the female parent of the early generation hybrid individual was P. mexicana and the male parent was P. velifera. Thus, while rare in the wild, interspecific hybridization and introgression between sailfin and shortfin mollies does occasionally occur despite the existence of behavioral pre-mating isolating mechanisms.